2010
DOI: 10.1136/bjsm.2009.067272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold water immersion on repeated cycling performance and limb blood flow

Abstract: The purpose of the present study was to compare the effects of cold water immersion (CWI) and active recovery (ACT) on resting limb blood flow, rectal temperature and repeated cycling performance in the heat. Ten subjects completed two testing sessions separated by 1 week; each trial consisted of an initial all-out 35-min exercise bout, one of two 15-min recovery interventions (randomised: CWI or ACT), followed by a 40-min passive recovery period before repeating the 35-min exercise bout. Performance was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
4
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 56 publications
10
107
4
5
Order By: Relevance
“…Similar to the current study, other researchers have reported that CWI performed immediately post-exercise resulted in benefit to subsequent exercise performed ~1 h (compared to active recovery; Vaile et al, 2010) and 24 h (compared to passive control; Bosak et al, 2006;Lane and Wenger, 2004) post immersion. In addition, Ingram et.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to the current study, other researchers have reported that CWI performed immediately post-exercise resulted in benefit to subsequent exercise performed ~1 h (compared to active recovery; Vaile et al, 2010) and 24 h (compared to passive control; Bosak et al, 2006;Lane and Wenger, 2004) post immersion. In addition, Ingram et.…”
Section: Discussionsupporting
confidence: 87%
“…It is also likely that the temperature of the water had a positive effect on subsequent exercise performance. Cold water immersion is proposed to reduce inflammation by evoking vasoconstriction (Peiffer et al, 2009) and decreasing peripheral blood flow (Sramek et al, 2000;Vaile et al, 2010). Vasoconstriction reduces the permeability of cellular, lymphatic and capillary vessels, which slows fluid diffusion into the interstitial space, therefore limiting oedema (Eston and Peters, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outros autores utilizaram a técnica de imersão por tempos menores como, 12 minutos (29) , dez minutos (17) , cinco minutos (30) e até um minuto de imersão (1) .…”
Section: Apresentação E Discussão Dos Resultados Crioterapiaunclassified
“…Para isso, tem-se utilizado algumas técnicas, como terapias manuais [4], termoterapia [1,2,5,9,12,13,15,23,29] e recuperação ativa (RA) [3,8,10,11,26].…”
Section: Considerações Finaisunclassified